2000
DOI: 10.1046/j.1365-2893.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilic patients with hepatitis C have higher viral load compared to other well‐defined patient groups

Abstract: Comparison of hepatitis C viral load between different patient populations has been hampered by the use of different technology in individual studies. We had the impression that haemophilic (HAEM) patients had a higher serum load of hepatitis C virus (HCV) compared to other HCV-infected patients. We therefore studied viral load and genotypes in active illicit drug users (IDU), HAEM patients and patients with post-transfusion hepatitis (PTH). The study comprises 225 HCV-RNA positive patients, 117 IDU, 60 HAEM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…It has been reported that HCV-RNA viral load was independently associated with haemophilic patients and genotype, but not to age, gender or disease duration (Krarup et al, 2000). We have also found that HCV-RNA viral load was not associated with age, gender, or mixed infection (Table 1).…”
Section: Discussionsupporting
confidence: 64%
“…It has been reported that HCV-RNA viral load was independently associated with haemophilic patients and genotype, but not to age, gender or disease duration (Krarup et al, 2000). We have also found that HCV-RNA viral load was not associated with age, gender, or mixed infection (Table 1).…”
Section: Discussionsupporting
confidence: 64%
“…Relatively rapid progression of HCV-mediated liver disease has been described in individuals with HIV-1-related immunodeficiency (21,47,53,54). There is also increasing evidence that infection with each of these viruses can alter the course of infection of the other virus (14,22,33), which has been hypothesized to be due to influences on immune responses. In coinfected individuals, HCV viral loads tend to be higher than in those infected with HCV alone (33).…”
mentioning
confidence: 99%
“…There is also increasing evidence that infection with each of these viruses can alter the course of infection of the other virus (14,22,33), which has been hypothesized to be due to influences on immune responses. In coinfected individuals, HCV viral loads tend to be higher than in those infected with HCV alone (33). Conversely, acute HCV infection can raise HIV-1 viremia in persons with otherwise well-controlled illness, and coinfection with HCV may accelerate progression from HIV-1 infection to AIDS (22).…”
mentioning
confidence: 99%
“…The prevalence of anti-hepatitis C virus (HCV) antibodies among 4 drug users has been reported to be between 62% and 97% (19)(20)(21)(22). Patients with hemophilia, patients undergoing hemodialysis, multi-transfused patients and patients originating from high endemic areas also have an increased prevalence of HCV infection (20,23). Seroprevalence surveys of the general population are the gold standard for determining the number of HCV-infected individuals within a country.…”
Section: Chronic Hepatitis Bmentioning
confidence: 99%